Catching up with wonderful women: The women-are-wonderful effect is smaller in more gender egalitarian societies - Krys, Kuba; Capaldi, Colin A.; Van Tilburg, Wijnand Adriaan Pieter; Lipp, Ottmar V.; Bond, Michael Harris; Vauclair, Christin Melanie; Manickam, L. Sam S; Domínguez Espinosa, Alejandra Del Carmen; Torres, Claudio; Vivian Miu Chi, Lun Miu Chi; Teyssier, Julien; Miles, Lynden K.; et al. (Wiley-Blackwell, 2018)
Inequalities between men and women are common and well-documented. Objective indexes show that men are better positioned than women in societal hierarchies-there is no single country in the world without a gender gap. In contrast, researchers have found that the women-are-wonderful effect-that women are evaluated more positively than men overall-is also common. Cross-cultural studies on gender equality reveal that the more gender egalitarian the society is, the less prevalent explicit gender stereotypes are. Yet, because self-reported gender stereotypes may differ from implicit attitudes towards each gender, we reanalysed data collected across 44 cultures, and (a) confirmed that societal gender egalitarianism reduces the women-are-wonderful effect when it is measured more implicitly (i.e. rating the personality of men and women presented in images) and (b) documented that the social perception of men benefits more from gender egalitarianism than that of women